2012
DOI: 10.1016/j.microrel.2012.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of IGBT thermo-sensitive electrical parameters under different dissipation conditions – Comparison with infrared measurements

Abstract: a b s t r a c tJunction temperature evaluation is a key parameter used to control a power module assembly. But measuring the junction temperature by thermo-sensitive electrical parameters (TSEPs) does not reveal the actual temperature of the semiconductor device. In this paper, a specific electronic board used to compare four common TSEPs of IGBT chips is presented. For this comparison, two dissipation modes are used: dissipation in active and saturation regions. In order to have referential measurements we ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…In each case, the temperature given by the TSEP is compared with the temperatures given by IR measurements. This figure shows that VCE_Ict gives temperature measurements between the mean and maximum temperatures as it was already demonstrated in [9,[19][20]. This TSEP is weakly influenced by the degradation because the difference between mean and TSEP temperatures decreases slightly (<2°C) when two bond wires are cut.…”
Section: Synthesissupporting
confidence: 72%
See 1 more Smart Citation
“…In each case, the temperature given by the TSEP is compared with the temperatures given by IR measurements. This figure shows that VCE_Ict gives temperature measurements between the mean and maximum temperatures as it was already demonstrated in [9,[19][20]. This TSEP is weakly influenced by the degradation because the difference between mean and TSEP temperatures decreases slightly (<2°C) when two bond wires are cut.…”
Section: Synthesissupporting
confidence: 72%
“…-one infrared (IR) camera is used to evaluate the surface temperature of the chips, -a classical TSEP is compared with the new TSEP: the forward voltage under low current. In the following sections, it will be called VCE Ict.It has been shown by various authors that this TSEP is robust and gives temperature measurements close to the mean temperature of the chip [18][19][20].…”
Section: Methods and Experimental Toolsmentioning
confidence: 83%
“…Discrepancies between the measured 'average' temperature via TSEPs and the actual temperature peak in the device have been identified as far back as 1966 [56] as well as in more recent studies [57]- [59]. It has also been demonstrated that alternate TSEPs can give varying temperature measurements on the same device under the same conditions, as well as having a dependence on dissipation mode [60] [61].…”
Section: Temperature Non-uniformitymentioning
confidence: 97%
“…The surface temperature of the prototype is measured by an infrared camera CEPIP-FLIR and a K-type open thermocouple placed at a corner of the leadframe. For infrared measurement, we deposit a 10µm-thick paint on the entire upper surface of the prototype which offers an emissivity of 0.93 in the functional wave length interval of the infrared camera [25]. Here we introduce only the validation of single-void simulation consisting in electrical and thermal comparisons.…”
Section: Experimental Validationmentioning
confidence: 99%